Distribution of gamma-ray bursts on the T90–HR plane and their classification revisited. Issue 4 (2nd November 2022) - Zhang, Liang; Luo, Juan-Juan; Huang, Yong-Feng; Gong, Yu-Jun; Wu, Sheng
ABSTRACT: Using four mixed bivariate distributions ( Normal distribution, Skew-Normal distribution, Student distribution, Skew-Student distribution) and bootstrap re-sampling analysis. We analyse the samples of CGRO/BATSE, Swift/BAT, and Fermi/GBM gamma-ray bursts in detail on the T 90 –HR (Hardness Ratio) plane. The Bayesian information criterion is used to judge the goodness of fit for each sample, comprehensively. It is found that all the three samples show a symmetric (either Normal or Student ) distribution. It is also found that the existence of three classes of gamma-ray bursts is preferred by the three samples, but the strength of this preference varies with the sample size: when the sample size of the data set is larger, the preference of three classes scheme becomes weaker. Therefore, the appearance of an intermediate class may be caused by a small sample size and the possibility that there are only two classes of gamma-ray bursts still cannot be expelled yet. A further bootstrap re-sampling analysis also confirms this result.